The Effectiveness of Snakes and Ladders Game on Mother's Activeness in Participating of Pregnant Women's Classes in South Amanatun District, Timor Tengah Selatan - Anggrawati Wulandari; Retno Palupi Yonni Siwi; Sonya Ana Maryanti Modu (Universitas STRADA Indonesia, 2022)
Pregnant Women Class was a means learning together about health for pregnant women in the form of face-to-face in groups, which aims to increase the knowledge and skills of mothers regarding pregnancy, prenatal care, childbirth, postpartum care, newborn care, myths, comorbidities. The lack of learning media in pregnant women's classes can have an impact on the activeness of mothers taking classes for pregnant women. Based on the initial study conducted by the researcher, there was a gap between expectations and reality, namely that the activeness of mothers could reach (100%) but in reality, it only reached (50%), because the delivery media in the pregnant women class only used leaflets, flip sheets and KIA books as well as the delivery method in the mother class.